New horizons of applied scanning electron microscopy - Shimizu, Kenichi (Springer, 2010)
In modern scanning electron microscopy, sample surface preparation is of key importance, just as it is in transmission electron microscopy. With the procedures for sample surface preparation provided in the present book, the enormous potential of advanced scanning electron microscopes can be realized fully. This will take the reader to an entirely new level of scanning electron microscopy and finely-detailed images never seen before.